THE IMPROVEMENT OF MATHEMATICAL CRITICAL THINKING ABILITY OF ELEMENTARY SCHOOL STUDENTS USING REACT STRATEGY - Eldi Fajri N; Taufina (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2020)
This research is motivated by the low critical thinking skills of elementary school students. The purpose of this research is to find out the improvement of students' mathematical critical thinking skills in elementary school by using REACT strategy. This research was a Classroom Action Research (CAR) conducted in grade 4 at SDN 02 VII Koto Sungai Sarik Padang Pariaman. The research procedure consisted of planning, implementing, observing, and reflecting. Data collection techniques used the method of observation, measurement of learning test results and documentation. The data analysis technique consisted of quantitative data. The results showed that an increase in students' mathematical critical thinking skills began with an initial ability of 43.67, cycle 1 gained an average of 68.56, and cycle 2 gained an average of 83.37. So it can be concluded that there was an increase in mathematical critical thinking skills of elementary school students by using the REACT strategy. This study recommends that elementary school teachers can use the REACT strategy as an effort to improve mathematical critical thinking skills of elementary school students.